Imaging Herpes Simplex Virus Type 1 Amplicon Vector–Mediated Gene Expression in Human Glioma Spheroids - Christine Kaestle; Alexandra Winkeler; Raphaela Richter; Heinrich Sauer; Jürgen Hescheler; Cornel Fraefel; Maria Wartenberg; Andreas H. Jacobs (Molecular Imaging)
Vectors derived from herpes simplex virus type 1 (HSV-1) have great potential for transducing therapeutic genes into the central nervous system; however, inefficient distribution of vector particles in vivo may limit their therapeutic potential in patients with gliomas. This study was performed to investigate the extent of HSV-1 amplicon vector–mediated gene expression in a three-dimensional glioma model of multicellular spheroids by imaging highly infectious HSV-1 virions expressing green fluorescent protein (HSV-GFP). After infection or microscopy-guided vector injection of glioma spheroids at various spheroid sizes, injection pressures and injection times, the extent of HSV-1 vector–mediated gene expression was investigated via laser scanning microscopy. Infection of spheroids with HSV-GFP demonstrated a maximal depth of vector-mediated GFP expression at 70 to 80 μm. A > 80% transduction efficiency was reached only in small spheroids with a diameter of < 150 μm. Guided vector injection into the spheroids showed transduction efficiencies ranging between < 10 and > 90%. The results demonstrated that vector-mediated gene expression in glioma spheroids was strongly dependent on the mode of vector application—injection pressure and injection time being the most important parameters. The assessment of these vector application parameters in tissue models will contribute to the development of safe and efficient gene therapy protocols for clinical application.